2015
DOI: 10.1111/cea.12536
|View full text |Cite
|
Sign up to set email alerts
|

Allergic conjunctivitis: a cross‐sectional study

Abstract: An understanding of ocular allergic disease, its incidence, demographics, and treatment paradigms provides important information towards understanding its pharmacoeconomics and burden on the national health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 20 publications
1
48
1
2
Order By: Relevance
“…Although several studies suggest a high comorbidity of conjunctivitis and rhinitis, conjunctival symptoms are often perceived by clinicians as a minor problem and suboptimally treated. A recent survey revealed that daily treatment of OA has little concordance with current recommendations . Topical ocular decongestants and corticosteroids were used in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies suggest a high comorbidity of conjunctivitis and rhinitis, conjunctival symptoms are often perceived by clinicians as a minor problem and suboptimally treated. A recent survey revealed that daily treatment of OA has little concordance with current recommendations . Topical ocular decongestants and corticosteroids were used in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…This was independent of the specific diagnosis of OA subtype and severity. Topical antihistamines and mast cell stabilizers, which are the first‐line therapy in most published recommendations, were used less frequently . The incorrect management of OA may increase the risk of local and systemic treatment‐related side effects .…”
Section: Introductionmentioning
confidence: 99%
“…About 60% of subjects used more than one medication. In fact, 40% of patients used a combination of decongestants and corticosteroids for ocular allergy, independent of the specific diagnosis [Leonardi et al 2015]. Thus, the habitual use of legacy medications persists in the face of evolved options having greater efficacy against ocular itching.…”
Section: Historical and Current Treatment Optionsmentioning
confidence: 99%
“…Nevertheless, approximately 27% of patients currently employ systemic antihistamines [Leonardi et al 2015]; presumably patients utilize OTC systemics as first-line treatment in absence of medical consultation.…”
Section: Second-generation Antihistaminesmentioning
confidence: 99%
“…3,[12][13][14] Moreover, people of different ages have different sensitive allergens. 15,16 Hence, local data of distribution of allergens are important and needed to be investigated. However, data elucidating the distribution of common allergens in Sichuan, Western China, are lacking.…”
mentioning
confidence: 99%